Longitudinal recovery and self-efficacy in first-episode schizophrenia: insights from a 10-year follow-up study - Anne-Kari Torgalsbøen; Christine Mohn; Frank Larøi; Frank Larøi; Nikolai Czajkowski; Nikolai Czajkowski (Frontiers in Psychiatry)
BackgroundResearch on clinical recovery rates in first-episode schizophrenia has yielded inconsistent results due to varying definitions of recovery and methodological differences. The longitudinal trajectory of recovery—whether rates improve, decline, or remain stable—remains unclear. Schizophrenia significantly impacts young lives, making it crucial to examine self-efficacy, the belief in one’s ability to manage adversity, and its relationship with clinical recovery.MethodsThe Oslo Schizophrenia Recovery study`s repeated assessment design, including twelve clinical evaluations over ten years, is ideal for studying longitudinal recovery. Self-efficacy was measured using the General Perceived Self-Efficacy scale, with data analyzed through linear multilevel models. Twenty-eight well-defined first-episode schizophrenia patients were assessed yearly, using a strict recovery definition (two years of full symptom remission and adequate social/role functioning), with 79% of patients retained from baseline.ResultsRecovery rates improved and remained stable, suggesting better outcomes than previously reported. Of the participants, 50% achieved clinical recovery. Recovered individuals showed a sharp increase in self-efficacy within the first year, while non-recovered patients exhibited gradual improvement. The interaction between recovery status and time revealed distinct self-efficacy trajectories, particularly in the first post-onset year.ConclusionsA significant proportion of first-episode schizophrenia patients can achieve clinical recovery. While these positive outcomes are noteworthy, it is important to recognize that recovery paths can vary widely among individuals. Since people with schizophrenia are concerned about their chances of recovery, the results must be shared with patients and their families. While the causal relationship between self-efficacy and recovery remains unclear, they likely influence each other.